2020
DOI: 10.1038/s41467-020-15006-4
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct modes of DNMT1 recruitment ensure stable maintenance DNA methylation

Abstract: Stable inheritance of DNA methylation is critical for maintaining differentiated phenotypes in multicellular organisms. We have recently identified dual mono-ubiquitylation of histone H3 (H3Ub2) by UHRF1 as an essential mechanism to recruit DNMT1 to chromatin. Here, we show that PCNA-associated factor 15 (PAF15) undergoes UHRF1-dependent dual monoubiquitylation (PAF15Ub2) on chromatin in a DNA replication-coupled manner. This event will, in turn, recruit DNMT1. During early S-phase, UHRF1 preferentially ubiqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
141
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(159 citation statements)
references
References 70 publications
(137 reference statements)
17
141
0
1
Order By: Relevance
“…S14D), which favors DNA methylation. It was previously shown that IFC-305 is able to stimulate proliferating cell nuclear antigen (PCNA) 31 , which together with a complex machinery, guides DNMT1 to hemi-methylated regions for regenerating 5mC on complementary DNA strand during replication [52][53][54][55][56][57] . As such, maintaining DNA methylation through increasing DNMT1-guiding proteins, as well as stimulating cell cycle components such as CDK4, CDK6 and cyclin D1 31 , could be an alternative IFC-305 mechanism of action which explains the retention of a proliferating phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…S14D), which favors DNA methylation. It was previously shown that IFC-305 is able to stimulate proliferating cell nuclear antigen (PCNA) 31 , which together with a complex machinery, guides DNMT1 to hemi-methylated regions for regenerating 5mC on complementary DNA strand during replication [52][53][54][55][56][57] . As such, maintaining DNA methylation through increasing DNMT1-guiding proteins, as well as stimulating cell cycle components such as CDK4, CDK6 and cyclin D1 31 , could be an alternative IFC-305 mechanism of action which explains the retention of a proliferating phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Encouraged by the results with the antiGFP nanobody, we proceeded to test two existing nanobodies against endogenous chromatin regulators, antiHP1 33 and antiDNMT 34 , for their capacity to silence and induce epigenetic memory. The antiHP1 nanobody was shown to bind to all three isoforms of HP1 33 , while the antiDNMT1 nanobody has previously been used to immunoprecipitate endogenous DNMT1 from whole cell lysate 34 . Using a similar system as the antiGFP nanobody, we cloned fusions between rTetR and either antiHP1 or antiDNMT1, and stably integrated them into HEK293T cells containing the TagRFP reporter with TetO sites at the AAVS1 locus ( Fig.…”
Section: Nanobodies Against Dnmt1 and Hp1 Can Silence A Reporter Genementioning
confidence: 99%
“…The cytoplasmic extracts were aliquoted and stored at -80˚C. Chromatin purification after incubation in egg extracts was performed as previously described with modifications (39). Sperm nuclei were incubated in egg extracts supplemented with an ATP regeneration system (20 mM phosphocreatine, 4 mM ATP, 5 μg /ml creatine phosphokinase) at 3000-4000 nuclei/μL at 22˚C.…”
Section: Xenopus Interphase Egg Extracts and Purification Of Chromatinmentioning
confidence: 99%